2014
DOI: 10.3103/s0967091214050118
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of metal oxides with carbon

Abstract: The reaction of metal oxides with carbon is investigated. Baikov's hypothesis regarding the role of atomic oxygen in the reduction of metals and the oxidation of carbon is confirmed theoretically and experi mentally. The initial stages in the process include conjugate chemical reactions: dissociation of the oxide with the liberation of atomic and molecular oxygen; and the oxidation of carbon. The reaction of thermodynam ically stable metal oxides with carbon is slowed by the accumulation of carbon monoxide in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 9 publications
11
25
0
Order By: Relevance
“…Especially prior to the moment of transition of the larger share of MoO 3 to lower oxide compounds, which possess vapor elasticity several orders of magnitude less [9]. This agrees with the results of research conducted by authors of articles [6,7,10] [10,15], from which it follows that obtaining a carbon-free product after carbon-thermal restoration is not possible. Spongy structure of the resulting metallized product makes it possible to relatively rapid dissolve in a liquid metal in the process of alloying, providing for a reduction in the losses of the target element.…”
Section: Discussion Of Results Of Examining the Indicators Of Propertsupporting
confidence: 80%
See 1 more Smart Citation
“…Especially prior to the moment of transition of the larger share of MoO 3 to lower oxide compounds, which possess vapor elasticity several orders of magnitude less [9]. This agrees with the results of research conducted by authors of articles [6,7,10] [10,15], from which it follows that obtaining a carbon-free product after carbon-thermal restoration is not possible. Spongy structure of the resulting metallized product makes it possible to relatively rapid dissolve in a liquid metal in the process of alloying, providing for a reduction in the losses of the target element.…”
Section: Discussion Of Results Of Examining the Indicators Of Propertsupporting
confidence: 80%
“…However, the products of restoration may contain residual carbon, bound in the oxy-carbide and carbide compounds [15]. This predetermines certain limitations in the use of resulting material without additional treatment for alloying the steels and alloys with limited carbon in their composition.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Thermodynamic calculations of reactions of WO 3 carbonothermia were carried out by the authors of work [5]. Transition of WO 3 to W 2 C and WC and then to W was most likely in the temperature range of 1,500−3,500 K. The probability of the presence of residual carbon bound in oxycarbide and carbide compounds of reduction products is also confirmed by authors in [6]. The study of the carbothermic reduction of tungsten oxides carried out by the authors of work [7] showed that this process passes through the stages of transition of WO 3 to WO 2.72 , WO 2 and W. The formed oxides are reduced to tungsten at 950 °C.…”
Section: Literature Review and Problem Statementmentioning
confidence: 86%
“…Carbonothermia is technologically simpler and is more attractive economically. But the reduction products may contain residual carbon bound in the oxycarbide and carbide compounds [2]. Moreover, Fe and Mo (as the basic alloying element of many brands of precision alloys) are the carbide-forming agents.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%